What Really Happened to British Inequality in the Early 20th Century? Evidence from National Household Expenditure Surveys 1890-1961 - Ian Gazeley; Andrew T. Newell; Kevin Reynolds; Hector Gutierrez Rufrancos (Institute of Labor Economics (IZA), 2017)
We estimate income/expenditure inequality in Britain, exploiting five household surveys, spanning the years 1890 to 1961, some of which we recovered and digitised. After adjusting for differences in scope and sampling, we find little change in inequality among worker households over the period and that the three decades after World War 2 were probably the low point of survey-based inequality measures in the eight decades since the late 1930s. Our findings are consistent with the evidence from wage censuses on the overall variance of earnings, which only falls marginally over the period. We argue this relative steadiness was the result of opposing proximate forces, one being the decline in manual skill differentials due largely to changing wage-setting institutions. On the other side was growth in the employment share of non-manuals, with their higher skill and wage variance. We also argue that two demographic factors also played their parts. The sharp decline in fertility in the early part of the century reduced inequality, while the emergence of pensioner households in the 1950s tended to increase inequality in the lower end of the distribution. Lastly, our work suggests a substantial downward revision in the estimated size of the fall in inequality through World War Two. We find a fall of between one and two Gini percentage points between 1937/8 and 1953/4, compared with the often-quoted Blue Book estimate of almost seven Gini percentage points.
Keywords: D31; J31; N14; 330; United Kingdom; inequality; wage differentials